PRA (Participatory Rural Appraisal) Technique as an Alternative for Development of Tourism Village Potential in Selur Village, Ngrayun District, Ponorogo Regency - Addiansyah, Nur Rofiq; Pratiwi, Septina Eka (Institut Agama Islam Negeri (IAIN) Kudus, 2022)
This paper shows that village development is an important program in community development. Of course, this development also relies on community participation. The tourism village cannot be separated from the participation of the community in it. The condition of the community will be the main factor in the interest of the ongoing process of developing a tourist village. When people are able to think properly and correctly, the management of natural resources will be better. The results of this research also show the results if the packaging of the tourist village will affect the results of the tourists who attend, because good creations and innovations will bring some good things or visitor participation will be better for the tourism manager and the surrounding community. To achieve this maximum result, one of the efforts is to use the PRA or Participatory Rural Appraisal method.This research method uses a qualitative method with the type of case study. The method of data collection was carried out by in-depth interviews and observation. For future research, it can be done by deepening the PRA technique in village development.